Using time-inconsistent wait-time functions for cycle-free coordinated traffic intersections. (June 2020) - Gravelle, Evan; Martínez, Sonia
Abstract: Sensing and computing capabilities of modern traffic intersections have greatly improved in recent years, but current control policies do not fully utilize these capabilities. In this paper, we present a novel intersection control algorithm based on an objective function that accounts for drivers' time preferences. In particular, the intersection places greater importance on a vehicle which has been waiting at an intersection over one that just arrived. Coordination between intersections is achieved through an added term to the objective function using the green wave idea. Under this policy given a macroscopic dynamical model, we provide a sufficient condition for the controller to maintain uniformly bounded weighted queues at an intersection given sufficiently small spawn rates. We test our algorithm and results extensively in a realistic microscopic simulation, through measuring queue stability and various performance metrics.